Bioestimulantes contendo silício e micronutrientes aplicados via foliar em arroz de sequeiro - Vasconcelos, Ana Carolina Pereira de (2016)
Despite the use of the most modern technologies of plant cultivation and the progress in breeding programs, the full potential of crops of agronomic interest is still far from being fully exploited. Biostimulants, a relatively new product category of various formulations, positively affect vital processes of plants and have shown great potential for use in the Brazilian agriculture, especially in the rice agriculture. The aim of this study is to discuss the use of hormonal regulation agrochemicals and assess the agronomic and nutritional efficiency of the foliar application of two biostimulants based on AZAL5 Technology (extract of Ascophyllum nodosum) containing potassium silicate and micronutrients. Chapter 1 draws on a review of the literature to discuss uses, concepts, benefits of and obstacles to biostimulants, bioregulators, bio-activators, humic and fulvic acids, as well as seaweed extract in the Brazilian agriculture. The following chapters report on two experiments (biological testing) that assessed both biostimulants – one containing potassium silicate + molybdenum (Chapter 2) and the other containing potassium silicate + zinc (Chapter 3) – applied to upland rice foliage. The experiments were carried out in a greenhouse, using 5-kg vases with Quartzipsamment soil and BRS Primavera cultivar. The experimental design was completely randomized, with four repetitions in a 5 x 2 structure. The treatments consisted of five doses (0; 1.50; 3.00; 4.50; 6.00 L ha-1) used in two modes of application (single application or in portions). The following parameters were evaluated: concentrations of chlorophyll A, B and Total; leaf content of macro and micronutrients and Si; and dry matter of root and aerial part. Statistical assumptions were assessed for the obtained data using Kolmogorov-Smirnov normality test and Levene’s test for homogeneity of variances, both set at 1%. Tukey’s test was used for analysis of variance and set at 5% significance. The significant data for the quantitative factor (doses) were included in a regression analysis. The application of biostimulant containing potassium silicate + molybdenum significantly changed the leaf content of K, Ca, S, Zn and Cu, as well as the production of dry matter of root. However, the leaf content of N, P, Mg, Fe, Mn and Si, the concentrations of chlorophyll A, B and Total, and the production of dry matter of aerial part were not significantly influenced by the different doses of said biostimulant and modes of application. The application of biostimulant containing potassium silicate + zinc significantly impacted on the leaf content of N, Ca, Mg, S, Zn and Cu, and on the production of dry matter of root. However, the leaf content of Si, P, K, Fe, and Mn, the production of dry matter of aerial part and the concentrations of chlorophyll A, B and Total were not significantly influenced by the different doses of said biostimulant applied in different modes.